Yield stability of durum wheat (Triticum durum desf.) in the region of the plains with petrocalcic subsoil layer of La Pampa province (Semiárida, 2020)
The objective of this work was to analyze the grain yield of durum wheat (Triticum durum Desf.) and its stability in the plains region, with petrocalcic subsoil layer, of La Pampa, Argentina. Five genotypes of durum wheat and two controls (bread wheat and triticale) were used during fíve growing seasons. Variability in grain yield was contributed in similar proportions by the environment, the genotype and the genotype x environment interaction. Variability of yield for some genotypes could be explained by the rainfall in October; however, winter-spring freezes should be taken into account in other cases. Triticale variety Eronga 83 showed the highest yield in all the environmental conditions. Durum wheats varieties Buck Crista and Bonaerense INTA Cumenay presented good stability with intermediate yield, while the bread wheat variety Buck Guaraní showed a significant instability. Eronga 83 was the only variety showing a preponderant yield component: the number of grains per spike. The results showed that high yields and stability are not mutually excluding. In conclusion, there are some non-traditional winter cereal genotypes for the plains region that could allow farmers to increase production, stability and diversity.
Keywords: durum wheat; yield stability; genotype by environment interaction